Features of 5′-splice-site efficiency derived from disease-causing mutations and comparative genomics - Roca, Xavier; Olson, Andrew J.; Rao, Atmakuri R.; Enerly, Espen; Kristensen, Vessela N.; Børresen-Dale, Anne-Lise; Andresen, Brage S.; Krainer, Adrian R.; Sachidanandam, Ravi

(untitled) (Genome Research, 2008)
Many human diseases, including Fanconi anemia, hemophilia B, neurofibromatosis, and phenylketonuria, can be caused by 5′-splice-site (5′ss) mutations that are not predicted to disrupt splicing, according to position weight matrices. By using comparative genomics, we identify pairwise dependencies between 5′ss nucleotides as a conserved feature of the entire set of 5′ss. These dependencies are also conserved in human–mouse pairs of orthologous 5′ss. Many disease-associated 5′ss mutations disrupt these dependencies, as can some human SNPs that appear to alter splicing. The consistency of the evidence signifies the relevance of this approach and suggests that 5′ss SNPs play a role in complex diseases.